AN ANALYSIS OF THE RELEVANCE OF ENGLISH MATERIALS IN TEXTBOOK ENTITLED “PATHWAY TO ENGLISH” FOR SENIOR HIGH SCHOOL GRADE X TO THE 2013 CURRICULUM (RETAIN, 2014)
AN ANALYSIS OF THE RELEVANCE OF ENGLISH MATERIALS IN TEXTBOOK ENTITLED “PATHWAY TO ENGLISH” FOR SENIOR HIGH SCHOOL GRADE X TO THE 2013 CURRICULUM Laras Ratnasari English Study Program FBS Surabaya State University larasratnasari@gmail.com Ririn Pusparini, S.Pd., M.Pd. Lecturer of English Study Program FBS Surabaya State University rrn.puspa@gmail.com ABSTRACT Recently, by Peraturan Pemerintah No.32 Th. 2013 the educational system of Indonesia has launched the 2013 curriculum. Due to the new launched curriculum, there are several changes in some parts of education, including the material. Textbook is one of the materials which have to give deep attention. A research from McGrath (2006) showed that mostly English language teacher use textbook as their main sources of teaching. Therefore, textbook should be matched with curriculum applied. However, selecting the best textbook is considering difficult for some teachers. Although there are many textbooks which are claims suitable with the 2013 curriculum, there is no guarantee whether the textbook is relevant to the standard competences of the 2013 English curriculum. To solve this problem, the researcher focused this study: 1) to describe the relevance of the materials in textbook entitled “Pathway to English” to the 2013 English Standard Competence in term of cognitive aspects, 2) to describe the relevance of the materials in textbook entitled “Pathway to English” to the 2013 English Standard Competence in term of psychomotor aspects. This study was designed in descriptive qualitative research. The instrument used to collect the data is observation in the form of checklists. After being analyzed, it is found that all chapters in the first semester successfully cover the indicators of cognitive aspects in the basic competences three. Meanwhile, some of the materials are irrelevant in terms of psychomotor aspects. After all, the researcher argues that this textbook is still appropriate to be used, since the materials are mostly relevant with the 2013 curriculum. This textbook is still suitable to be used in order to help teacher and students in the process of teaching and learning. Key words: analysis, relevance, materials, textbook, the 2013 Curriculum ABSTRAK Baru-baru ini, melalui Peraturan Pemerintah No.32 Th. 2013 pemerintah Indonesia meluncurkan kurikulum 2013. Karena adanya peluncuran kurikulum baru ini, ada beberapa perubahan dalam beberapa bagian di sistem pendidikan termasuk di material. Buku teks adalah salah satu material yang harus diberi perhatian. Riset dari McGrath (2006) menunjukan bahwa sebagian besar guru bahasa Inggris menggunakan buku teks sebagai sumber utama dalam mengajar. Oleh karena itu, buku teks haruslah sesuai dengan kurikulum yang berlaku. Namun, memilih buku teks terbaik itu tidaklah mudah bagi beberapa guru. Meskipun banyak buku yang mengklaim sesuai dengan kurikulum 2013 namun, tidak ada jaminan apakah buku itu benar-benar relevan dengan kompetensi dasar dari kurikulum 2013. Untuk mengatasi masalah ini, peneliti memfokuskan penelitian ini: 1) untuk mendeskripsikan kesesuaian material buku teks berjudul ‘Pathway to English’ dengan kompetensi dasar bahasa Inggris kurikulum 2013 sesuai dengan kognitif aspek, 2) untuk mendeskripsikan kesesuaian material buku teks berjudul ‘Pathway to English’ dengan kompetensi dasar bahasa Inggris kurikulum 2013 sesuai dengan psikomotor aspek. Metode penelitian yang digunakan dalam penelitian ini adalah deskriptif kualitatif. Instrumen yang digunakan untuk mengumpulkan data adalah observasi dalam bentuk checklist. Setelah dianalisis, ditemukan bahwa semua bab dalam buku teks ini dapat memenuhi semua indikator dari kognitif aspek dalam kompetensi dasar tiga. Sedangkan, sebagian material ada yang tidak sesuai dengan psychomotor aspek. Meskipun demikian, peneliti berargumen bahwa buku teks ini masih cocok untuk digunakan, karena sebagian besar materinya telah sesuai dengan kurikulum 2013. Buku teks ‘Pathway to English’ ini masih bisa digunakan untuk membantu guru dan murid dalam proses mengajar dan belajar. Kata kunci: analysis, relevance, materials, textbook, the 2013 Curriculum Introduction Realizing the importance of English language in globalization era, recently, Indonesian government has implemented English subject into the academic curriculum as a compulsory subject to be taught in Junior and Senior High school. Recently, by Peraturan Pemerintah No.32 Th. 2013 the educational system of Indonesia has launched the 2013 curriculum. This new launched curriculum is a school based curriculum, an operational curriculum which is constructed, developed, and implemented by each education unit (school). The aim of this curriculum is preparing Indonesian people to be religious, productive, creative, and innovative. Furthermore it is hoped that they also can give contribution for their social life, nation, country and world civilization. Due to the new launched curriculum, there are several changes in some parts of education. As stated by Richards (2001:103), Curriculum changes are of many different kinds. Curriculum may affect teachers’ pedagogical values and beliefs, teachers’ understanding of the nature of language or second language learning, or their classroom practices and the use of teaching and learning materials. Among several changes in education parts teaching material also need to be adjusted because it is one of the most important factors in teaching and learning process. This argument is supported by Richards (2001). He argues teaching materials are regarded as a key factor in most language programs. Teaching materials can be developed from many learning sources, one of it is from textbook, thus, it also need special attention regarding its changes toward recent applied curriculum. The adjustment of textbook to the recent curriculum should be conducted because English teachers tend to display a strong reliance on textbook usage. In a research by Richards, Tung & Ng as cited by Lawrence (2011) they conducted a research with 149 local secondary school English teachers, it was reported that textbook were one of the primary sources of teaching material. Only 28% of the total respondents have claimed that they have made a significant use of self-developed teaching materials. In addition for the use of textbook in English language teaching, the research from McGrath (2006) also showed that mostly English language teacher use textbook as their main sources of teaching. The study involved 75 teachers of English, mainly English teachers of secondary schools, and several hundreds of secondary school students. It was found that teachers mostly think that the use of textbooks is important. The wide use of textbooks in the local ELT classroom is understandable as given the fact that material (textbooks) are not simply the everyday tools of the language teacher, they are embodiment of the aims, values and methods of the particular teaching and learning situation (Hutchinson: 1987). A good textbook should be reflected the curriculum which is applied. It is because there is a strong relationship between both of them. The relationship of textbook and curriculum can be described as water and fish, or as the two sides of coin, two but one, one but two (Tarigan and Tarigan, 1986: 66). It should be matched with the goal of the curriculum and be able to support curriculum and facilitate the process of teaching and learning. Every curriculum has their own goals which have to be reached by students as the sign of their success and expertness in their education. One of the goals in curriculum is instructional objective. It describes what behavior and ability that the students need to reach after teaching and learning process. Instructional objective should depict the learning objective which is expected from the students. The learning objective which is expected is behavior change of the students. The forms of students’ objective behavior are classified into three domains by Bloom et. al.(1956). They named it as “The taxonomy of educational objectives”. Objectives could be placed in one of three major domains or classification; (1) Cognitive, (2) Affective, and (3) Psychomotor. Thus every textbook written nowadays should be applied those three objectives as one of qualification of a suitable textbook based on 2013 curriculum because it is the recent curriculum applied in Indonesia. Despite the need of a suitable textbook for teachers and students, selecting an appropriate textbook with a good quality and curriculum matched is not easy. Cunningsworth and Green in Lawrence (2011) stated that the increasing of textbook on the market makes it difficult to choose the right textbooks. Therefore, the selection of textbook should be conducted seriously because it can have massive impact on the teaching and learning process as teachers would make references to the textbooks. (Cunningsworth, Harmer, McGrath in Lawrence, 2011). One wrong step in choosing an appropriate textbook can lead into the failure in teaching and learning process. It is supported by Mukundan (2007) that the quality of a textbook might be so important that it can determine the success or failure on ELT courses. Unfortunately, not all textbooks are written in a good quality in terms of its appropriateness with teacher and students’ need or its compatibility with applied curriculum. Teachers as the determiner of teaching process in class sometimes careless in choosing the right textbook for their students. In line with this argument, McGrath (2002) showed that textbooks are often purchased without careful analysis. Frequently, a textbook selection is not based on its intrinsic pedagogical value, but the perceived prestige of the author or the publisher, or skillful marketing by the publishers. The books are printed in attractive covers or teachers only blindly use the best-selling textbooks which are used in many other places. (McGrath 2002) It is regrettably consider the significant of textbook in teaching and learning process. There are various textbook written by expert writers which are claimed based on the 2013 curriculum. However, though the textbook written by professional writers are usually of good quality in terms of organization, packaging and design, they tend to be lacking in qualities of being creative and imaginative (Tomlinson, 2003). Besides, the urgency to evaluate ELT textbooks written for the new curriculum on its pedagogical fitness with the recommended instructional objectives has become an urgent concern as many local English teachers have displayed heavy reliance on textbooks in their daily teaching (Lawrence, 2011). There are some previous studies related to the textbook analysis. Some of them are Widiarto (2009) and Fauzi (2012). They analyse the relevance of textbook materials with 2006 English Standard Competence. Widiarto (2009) found that there are some conformity of the text materials in the textbook. However, not all of the text materials which are suggested in standard isi 2006 are developed in four language skills in the textbook. Meanwhile, Fauzi (2012) found that all of reading materials are not relevant to the 2006 English Standard Competence. It did not provide any explanations, examples, and exercises in order to make the students really understand about the texts being learnt. Thus, it is proven that not all the textbook used are relevant to the curriculum. In addition, although the 2013 curriculum is already applied in Indonesian education system, there is still lack analysis of textbook which based on the 2013 Curriculum, since the 2013 curriculum is still fresh launched in 2013. According to those reasons stated, this study is aimed to analyze and figure out the relevance of materials of English textbook entitled “Pathway to English” for Senior High School published by Erlangga with the 2013 English Standard Curriculum in terms of Cognitive and Psychomotor aspects. RESEARCH METHOD Since this study deals with analysis of the content of the textbook especially in the form of document book, a descriptive qualitative research design will be implemented. Furthermore, Ary, D. et.al (2010: 423) stated that qualitative research mostly relies on words only minor use of numbers. Thus, the data which was derived is in the form of document from textbook then those data were described in the form of words without using statistical calculation. The object and the source of the data of this study is an English textbook entitled “Pathway to English” for Senior High School Grade X Published by Erlangga. This textbook is written by Th. M. Sudarwati and Eudia Grace. The textbook consists of 11 chapters and 248 pages. The materials of each unit are organized into 8 parts; (1) listening, (2) speaking, (3) reading, (4) writing, (5) grammar, (6) values, (7) cultural awareness, and (8) ways to say it. The researcher focused on just one book and all of the activities in the textbook in the scope of first semester, therefore, the research only focused at chapter 1 until chapter 5. The data gained from this research then analyzed using two research instruments. The first instrument was the researcher herself as the main instrument to collect the data. As stated by Ary,D. et.al (2010: 421) The primary instrument used for data collection in qualitative research is the researcher him- or herself, often collecting data through direct observation or interviews. The second instrument was the observation in the form of checklist. The data from this study was collected through several steps of observation. First, the researcher determined the textbook which is going to be analyzed through some survey on various textbooks which claimed based on the 2013 Curriculum on its cover. Second, the researcher read and observed the content of the textbook thoroughly. Third, the researcher will compare the content of the textbook with the 2013 Curriculum in terms of cognitive and psychomotor aspects. After being collected, the data was analyzed through some steps. First, the researcher analyzed the relevance of the materials with the cognitive aspects which are contained in the 2013 English Standard Competence. Second, the researcher analyzed the relevance of the materials with the psychomotor aspects which are contained in the 2013 English Standard Competence. Third, the researcher described and elaborated the analysis. The last, the researcher determined the conclusion. RESULT AND DISCUSSION The Relevance of ‘Pathway to English’ Textbook to the 2013 English Standard Competences In this section there will be some example of the tables of observation sheet and also the discussion to figure out the results of the relevance of ‘Pathway to English’ textbook material with the 2013 English Standard Competences. Each observation sheet for cognitive aspect in basic competence three is consisted of three columns. The first column will be divided into three aspects of the 2013 English curriculum, including Topic, Text structure, Language feature and also Social function. The second column is the example of activity in the textbook which is suitable with the 2013 English curriculum. the last column is the relevance of the material. for tables of psychomotor aspect in basic competence four it is also consisted of three columns but the first column will be divided into two aspects. It is including Topic and indicators only. The researcher used the third and fourth basic competences to analyze the relevance of the textbook material. The basic competences then broke down into sub-basic competences. In the following tables, the sign (√) means that the sub-basic competency and the material are relevant. Meanwhile, the sign (-) means the material are not relevant with sub-basic competence. The Relevance of the Materials with the Cognitive Aspects The table below is the result of the analysis of the relevance of textbook material with the 2013 curriculum in terms of cognitive aspects. Table 1. The conformity of textbook materials with the cognitive aspects The Relevance The Third Basic Competence Relevant All chapters in first semester Partly Relevant - Irrelevant - According to the table above, it can be seen that there is no partly relevant or irrelevant materials in chapter one to chapter five. All the materials in those chapters are relevant to the 2013 English curriculum in terms of cognitive aspects in basic competences three. All materials successfully provided the indicators needed in each sub-basic competence including the topic, the text structure, the language features and also the social function. The Relevance of the Textbook Materials with the Psychomotor Aspects Table 1. The conformity of textbook materials with the cognitive aspects The Relevance The Third Basic Competence Relevant 4.2.1, 4.2.2, 4.3.1, 4.3.2, 4.4.1, 4.4.2, 4.5.1, 4.5.2, 4.6.1, 4.6.2 Partly Relevant 4.1.1 and 4.1.2 Irrelevant - In the table above, it can be seen that there are some materials which are relevant and partly relevant with the psychomotor aspects in basic competence four. The relevant material successfully provided the indicators needed in each sub-basic competence four. The irrelevant materials cannot cover all the indicators in the sub-competences 4.1.1 and 4.1.2 both of the chapters do not include indicators ‘Find the purpose of the text’ which is one of the indicators of understanding the text. Thus, it can be concluded that the textbook materials is partly relevant with the basic competence four. CONCLUSION & SUGGESTION Conclusion The conclusion from the analysis can be subtracted into two points. The first point is the materials in the textbook ‘Pathway to English’ are all relevant with the cognitive aspects which are contained in the 2013 English Standard Competence. There are ten analysis tables for basic competences three. From all the ten tables, the researcher found that all the materials are relevant to the sub-competences in basic competences three. Therefore, the researcher concluded ‘The Pathway to English’ English textbook is relevant to the 2013 English curriculum in terms of cognitive aspects which are shown in basic competences three. Meanwhile, in the second point the researcher concluded that the materials in the textbook ‘Pathway to English’ are quite relevant with the psychomotor aspects in the 2013 English Standard Competence. There are twelve tables for the analysis of basic competences four. From twelve tables, there are two tables which showed that the materials in this textbook are not fully relevant to sub-competences which are tables for sub-competences 4.1.1 and 4.1.2. Another ten tables showed that the materials are relevant because it contains the materials for the sub-competences. According to the analysis above, the final conclusion states that material in the textbook ‘Pathway to English’ is still quite relevant with the 2013 English curriculum in terms of cognitive and psychomotor aspects. Since, the researcher found the materials which are relevant to sub-basic competence are more than the irrelevant one. Therefore, the researcher argues that this textbook is appropriate to be used as the aid material in English teaching and learning process. Suggestions After the analysis of this textbook ‘Pathway to English’, the researcher would like to give suggestions for: a) For teacher, they should be aware of what kind of textbook which is most suitable with their need. Since the process of teaching and learning depend on the curriculum, the teacher should be selective and careful to choose the most suitable textbook which covers the curriculum aims. The selected textbook should support the curriculum to achieve the instructional objectives. b) For the textbook writers/publishers, they have to apply the criteria in developing the materials. For this period of time, the materials should be in line with the 2013 English Standard Competence stated in the 2013 curriculum. Furthermore, the writers/publishers should be able to serve the high quality textbook which is able to fulfill all of the indicators, topics, language features, text structure and the social functions related to the competences. c) For the textbook writer of ‘Pathway to English’, they should concern more in conducting questions related to sub-competences understanding the texts. In order to be able to cover all the indicators stated in the sub-competences. d) For further research, the researcher hopes that in the future there will be another research regarding to analyze textbook with the 2013 Curriculum. The next researchers can conduct their research for the same textbook but focus on the activities in second semester. Otherwise, they can conduct research for another textbook with different grade. REFERENCES Ary, Donald. et.al. 2010. Introduction to Research in Education.Canada: Wadsworth, Cengage Learning. Bloom B. S. 1956. Taxonomy of Educational Objectives, Handbook I: The Cognitive Domain. New York: David McKay Co Inc. Byrd, P. 2001. Textbook: Evaluation for Selection and Analysis for Implementation. In M. Celce-Murcia (Eds.), Teaching English as a Second or Foreign Language (3rd ed., pp. 415-427). US: Heinle&Heinle. Fauzi, Arif. 2012. An analysis of Reading Materials in “Interlanguage: English for Senior High School Students XI (Science and Social Study Programme)” Published by The National Education Departement as An Implementation of The 2006 English Standard Competence. UNESA: Unpublished Thesis. Hutchinson, T. 1987. ‘What’s Underneath?: An Interactive View of Materials Evaluation’. In L. Sheldon. (Ed). ELT Textbook and Materials: Problems in Evaluation and Development (pp. 37-44). Oxford: Modern English Publications. Lawrence , W. 2011. Textbook Evaluation: A Framework for Evaluating the Fitness of the Hongkong New Secondary School (NSS) Curriculum. Department of English City University of Hongkong: Hongkong. McGrath, I. 2002. Materials Evaluation and Design for Language Teaching. Edinburgh: Edinburg University Press. Mukundan, J. 2007. Evaluation of English Language Textbooks: Some Important Issues for Consideration’. Journal of NELTA, Vol 12 No1&2: 80-4. Peraturan Menteri Pendidikan Dan Kebudayaan No.69 Th. 2013 . 2013. Kerangka Dasar Dan Struktur Kurikulum Sekolah Menengah Atas/Madrasah Aliyah. Jakarta: Mendikbud. Richards, Jack. 2001. Curriculum Development in Language Teaching. USA: Cambridge University Press. Tarigan, H. G and Tarigan, D. 1986. Telaah Buku Teks Bahasa Indonesia. Bandung Angkasa. Tomlinson, B. 2003. Developing Materials for Language Teaching. London: Continuum. Widiarto, Yos. 2009. A Study On The Relevance of English Textbook “Look A Head” Materials with Standar Isi 2006. UNESA: Unpublished Thesis.